Key Success Factors for Serving the Bottom of the Pyramid with Reference to Telecommunication Companies - Pudiyavalappil, Suresh Makkuni (2006)
Four leading telecommunication companies from four different countries are studied with the purpose of investigating whether a link can be established between theories for key success factors and the real business scenario with regard to Bottom of the Pyramid. The four companies analyzed are Grameen Phone (Bangladesh), Reliance Infocomm (India), Smart Communications Inc. (Philippines) and Vodacom (South Africa).The findings reflect a clear link between the selected theoretical parameters and actual business practice. Even though the parameters were present in varying degree, the overall analysis suggests the presence of these factors. The study is based on the consideration of the population at the Bottom of the Pyramid as both customers and co-creators of value. The innovative business processes and the resultant economic and social benefits derived by both company and the society are also illustrated. Study reflects that by adopting these key factors for success telecommunication companies can benefit from the vast potential of this largely untapped market. Lastly, specific recommendations to telecommunication companies interested to enter this market are provided.